Ownership and Performance of Lithuanian Enterprises - Grigorian, David A. (World Bank, Washington, DC, 2015)
The author presents some evidence of improved corporate performance in Lithuania for the period 1995-97. His question: Were these improvements in any way caused by privatization and changes in the environment in which enterprises operate? He presents evidence of correlation between ownership and enterprise performance as measured by increased revenues, and improved export performance. Controlling for pre-selection bias increases the magnitude, and significance of private share ownership, which indicates negative selection bias at privatization. On the other hand, (expected) subsidies seem to contribute negatively to enterprise performance. However, the study finds no clear evidence of the effect of market competition on performance indicators in the short run. The author's is the first study to analyze the consequences of commercial (as opposed to mass) privatization in Central and Eastern European countries.